The influence of visitors' specific motor actions on the perception and evaluation of museum exhibits - Tetiana Yermakova; Sergii Iermakov; Mateusz Tomanek; Wladyslaw Jagiello; Lidiya Zavatska (IP Iermakov S.S., 2023)
Background and Study Aim. An important element in the system of museum activities are approaches to attracting visitors. Among these approaches, one can single out the dialogue of the museum with visitors through specially organized active motor actions. Such actions have certain parameters (the nature of physical activity and its age-appropriateness, intensity, duration, etc.), which can influence the perception and evaluation of exhibits and the decision of visitors to return to the museum. The purpose of the study is an attempt to explain how specially organized active motor actions of visitors affect the perception and evaluation of museum exhibits and getting satisfaction from visiting. Material and Methods. Publications from the Web of Science Core Collection (WoS) were selected as the source of information. The search was carried out using keywords that characterize the interaction of visitors with the subject-spatial environment of the museum. The VOSviewer program was used to analyze the relationships between documents retrieved from WoS. Results. It is argued that the sedentary behavior of visitors, typical for many museums, does not contribute to their involvement in the museum space and the creation of meaning in museums. It is noted that an important aspect in the organization of special motor actions of visitors is the orientation to their motivation and interpretation of movements in the museum exhibits. The optimal level of physical activity has been identified. It creates a comfortable feeling and contributes to an adequate perception of the exhibits and corresponds to the main mission of the museum. Conclusions. Specially organized motor actions form the maximum motivation for visitors to study the museum exhibits. Such movements carry a certain semantic character of the theme of the museum.